Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 28. Beitrag: Hymenoptera: Ichneumonidae I (Ephialtinae). - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The expedition of the Deutsches Entomologisches Institut collected 17 specimens (9 species) of subfamily Ephialtinae (Tribus Pimplini and Ephialtini). All species found are new to the fauna of Albania.